YES1 amplification confers trastuzumab–emtansine (T-DM1) resistance in HER2-positive cancer - Wang, Lei (Br J Cancer, 2020)
BACKGROUND: Trastuzumab–emtansine (T-DM1), one of the most potent HER2-targeted drugs, shows impressive efficacy in patients with HER2-positive breast cancers. However, resistance inevitably occurs and becomes a critical clinical problem. METHODS: We modelled the development of acquired resistance by exposing HER2-positive cells to escalating concentrations of T-DM1. Signalling pathways activation was detected by western blotting, gene expression was analysed by qRT-PCR and gene copy numbers were determined by qPCR. The role of Yes on resistance was confirmed by siRNA-mediated knockdown and stable transfection-mediated overexpression. The in vivo effects were tested in xenograft model. RESULTS: We found that Yes is overexpressed in T-DM1–resistant cells owing to amplification of chromosome region 18p11.32, where the YES1 gene resides. Yes activated multiple proliferation-related signalling pathways, including EGFR, PI3K and MAPK, and led to cross-resistance to all types of HER2-targeted drugs, including antibody-drug conjugate, antibody and small molecule inhibitor. The outcome of this cross-resistance may be a clinically incurable condition. Importantly, we found that inhibiting Yes with dasatinib sensitised resistant cells in vitro and in vivo. CONCLUSIONS: Our study revealed that YES1 amplification conferred resistance to HER2-targeted drugs and suggested the potential application of the strategy of combining HER2 and Yes inhibition in the clinic.